Duffy blood group system – the frequency of Duffy antigen polymorphisms and novel mutations in the Polish population. (April 2019) - Łukasik, Ewa; Nowak, Izabela; Czerwinski, Marcin; Waśniowska, Kazimiera
Abstract: Duffy blood group genes are highly polymorphic with the distribution of alleles varying between different populations and ethnic groups. The aim of this study was to genotype Duffy blood group antigens and to establish FY alleles frequency in the Polish population and screen for novel FY gene mutations. Duffy phenotype and genotype frequencies analysis was based on studies of 596 persons. All these subjects were genotyped by high-resolution melting (HRM) method. It was shown that phenotype Fy(a+b+), defined by genotypes FY*A/FY*B (33%), FY*A/FY*B298A (13%), and FY*A/FY*02W.01 (2.8%) was the most common in Polish population (˜49%), followed by Fy(a−b+), ˜29%, determined by genotypes arising from FY*B allele and all its variants. Fy(a+b−) phenotype occurred with a frequency of 21.3% and was defined by the following genotypes: FY*A/A (21%), and FY*A/02N.01 (0.3%). Among the Polish population the frequencies of FY*A, FY*B, and FY*B298A alleles were 45.7%, 36% and 15.5%, respectively. The alleles FY*B298A and FY*B combined together, represented higher frequency (51%) than FY*A . Alleles FY*02W.01 and FY*02N.01 had frequencies 2.51% and 0.25%, respectively. The distribution of Duffy genotypes in the Polish population was in accordance with Hardy-Weinberg equilibrium (p = 0.9682). Alleles in the genotypes are independent from each other (r = 0.0278, R 2 = 0.00077). New mutations identified in the promoter region (c.-79T > C) and the coding region of the FY gene (c.147C > A and c.175 G > A) did not affect the Duffy antigen expression on erythrocyte. Although FY alleles frequency is known in different populations, no data for Polish population is available.